Akteursperspektiven auf Beteiligung an der Stadtteilentwicklung. - Schröder, Carolin (My University, 2007)
Ziel der Arbeit ist die Untersuchung von Perspektiven auf informelle Beteiligung an der Stadtteilentwicklung. Durch interdisziplinäre Literatur- und Internetanalysen sowie drei Fallstudien mit leitfadengestützten Interviews in Berliner Quartieren (Magdeburger Platz, Sparrplatz, Wrangelkiez) werden diese Perspektiven exploriert. In der Analyse zeigt sich, dass Akteure in der Praxis ähnliche Perspektiven auf Handeln in Beteiligungsprozessen haben und dass diese Perspektiven weniger auf Akteursgruppen zurückzuführen sind, denn auf subjektiv eingeschätzte Handlungsmöglichkeiten, Akteurskonstellationen und Rahmenbedingungen in den Quartieren. So spielt zum Beispiel die Produktion sichtbarer Ergebnisse für die Akteure eine wichtige Rolle, sie gilt sogar als entscheidendes Bewertungskriterium für den Erfolg der Beteiligungsprozesse bzw. eigenen Engagements. Darüber hinaus wurde deutlich, dass individuelles Handeln immer auch im Kontext aller Akteure gesehen wird. So wurde zum Beispiel akteursgruppenübergreifend auf die Bedeutung direkter Kommunikation, Rückkopplung, gegenseitiger Wertschätzung und ähnlicher Rechte bzw. Pflichten aller Akteure verwiesen und Motivationen bzw. Demotivationen durch Bürger, Verwaltungs- und Politikakteure sowie Quartiermanager beschrieben. Auch die Transparenz der Rahmenbedingungen, Strukturen, Rollen und verfügbaren Ressourcen wurde als wichtige Voraussetzung für eine Einschätzung individueller Handlungsmöglichkeiten benannt. Die Ergebnisse bieten für die Praxis konkrete Hinweise, wie die begriffliche Vielfalt von "Beteiligung an der Stadtteilentwicklung" besser gefasst werden kann. Für die Forschung zu Beteiligung auf Stadtteilebene ist es darüber hinaus sinnvoll, diese Übertragbarkeit der Ergebnisse dieser Arbeit Erfahrungen anhand systematisierter Ergebnisse aus der Praxis zu überprüfen und ggf. existierende wissenschaftliche Beschreibungs- und Erklärungsmodelle zu Akteurshandeln und Beteiligung auf Stadtteilebene zu hinterfragen.

When discussing participation in neighbourhood development, the multiple meanings und operationalisations of the term may cause misunderstandings. The objective of this study is to analyse and compare perspectives on informal participation in neighbourhood development in both theory and practice. Methods applied are interdisciplinary analyses of literature and internet documents as well as three case studies with guided interviews in Berlin neighbourhoods. The initial assumption was that different perspectives on participation do exist in practice just as they do in the literature, and that those different perspectives refer to differing individual interests, motivations and expectations. In addition, it was assumed that participatory processes - and actors involved - will depend more on interaction and mutual reference points (e.g. common objectives, definitions, action principles, synergy effects), which have been neglected in scientific models of action. After conducting the study, there is evidence thatactors in participatory processes have similar perspectives regarding action and interaction. But those perspectives can only partially be attributed to actor groups, they rather depend on subjective assumptions of options for action, actor s constellation and basic conditions in the neighbourhoods. E.g. the production of visible results played a major role for the actors which even proved to be a major success criterion for participatory processes and individual engagement. It then became obvious that individual action is seen in context of all actors involved as, throughout actor s groups, the significance of direct communication, feedback, mutual appreciation and similar rights and duties of all actors had been emphasized, In addition, motivations resp. demotivations as consequences of citizens, administrators, politicians and intermediary actors acting principles were specified. In addition, the transparency of basic conditions, structures, roles and available resources had been named as an important precondition for estimating individual ranges of action. Nonetheless, the interviewees defined participation in neighbourhood development differently, describing specific forms, grades, role ascriptions and action principles. Furthermore, they questioned the wide-spread association of participation processes with civil engagement, local democracy and quality of life. Those results from practice may help to narrow down the multiple meanings of "participation in neighbourhood development". Consequently, research on participation in neighbourhood development should verify resp. disprove the transferability of those results by systematising practical experiences on a larger basis and, if necessary, by questioning existing scientific assumptions on actors and participation.
Actor's perspectives on participation in neighbourhood development.
Keywords: Stadtentwicklungsplanung; Stadtteilplanung; Partizipation; Beteiligungsverfahren; Betroffenenbeteiligung; Gemeinwesenarbeit; Verwaltungshandeln; Fallstudie; Quartiermanagement; Motivation; Soziale Stadt; Empirische Untersuchung